Migrant transfers as a development tool: The case of Somalialand - Peter Hansen (Danish Institute for International Studies (DIIS), 2004)
This paper examines the relationship between migration and development in the contest of Somaliland, where an estimated 25-40 per cent of the population receive regular remittances from abroad. The importance of remittances to the local economy and the impact of diaspora activities on local development are the main focus of the paper. In distinguishing four main waves of migration the paper presents a short history of the formation of the Somali diaspora. The paper also estimates the volume, importance and social distribution of individual and collective remittances to Somaliland. Finally the paper gives an overview of the functioning financial institutions in Somaliland and identifies the challenges ahead for an economy that is heavily dependent on remittances.
Keywords: 330; Rücküberweisung (Migranten); Entwicklung; Somalia